BAHASA MASUK PORTUGIS KURIKULUM DALAM PEMBERITAAN DI MEDIA MASSA: ANALISI WACANA KRITIS - Rully Sulistyawan P.A; Cindy Angelina Putri Tambunan; Mazaya Elya Sakinah (Jurnal Padamu Negeri, 2026)
This research aims to uncover the representation of power and ideology in media coverage regarding educational policy. The focus of the study is directed at a news article from Kompas.com titled "Bahasa Portugis Masuk Kurikulum, Legislator Khawatir Akan Membebani Siswa" (Portuguese Language Enters the Curriculum, Legislators Fear It Will Burden Students), published on October 25, 2025. The central issue examined is the ideological contestation between the government's discourse on language internationalization and the discourse of academic efficiency voiced by the legislature. This study employs a qualitative approach using Norman Fairclough’s Critical Discourse Analysis (CDA) model. This approach views language as a social practice that maintains a dialectical relationship with social structures and power. Data were collected through literature study and the observation method (metode simak), utilizing digital document recording and repeated reading techniques to identify lexical choices and representational strategies. Data analysis was conducted through Fairclough’s three-dimensional framework: textual analysis (linguistic and lexical choices), discourse practice (processes of text production and consumption), and social practice (political context and power relations). The results indicate that the use of dictions such as "khawatir" (worry) and "bebani siswa" (burden students) functions as a framing strategy that represents the policy negatively. Data validity was ensured through theory and source triangulation to verify emerging discourse patterns. Overall, this study concludes that mass media possesses symbolic power in shaping public opinion and constructing social reality through non-neutral linguistic choices. This research contributes to the understanding of the media's role in mediating interest conflicts between policymakers and state institutions.